2012
DOI: 10.1016/j.apgeochem.2011.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic data provided through the FUNMIG project: Analyses and prospective

Abstract: International audienceIn this paper some of the needs for good quality thermodynamic data in radioactive waste management are highlighted. A presentation of the thermodynamic data produced within the 6th EC framework programme integrated project FUNMIG (Fundamental processes of radionuclide migration) and how these have helped in filling relevant thermodynamic data gaps is given. The manuscript does not intend to be a complete review of thermodynamic data, but a short overview of the aqueous complexation of Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The presence of silicate is ubiquitous in most natural groundwater systems, where total silicate concentrations may reach up to 10 −3 M. 129 In cementitious environments, which are considered in some concepts for the disposal of low and intermediate level radioactive wastes (L/ILW), silicate concentrations of up to ∼5 × 10 −4 M have been determined in pore water during the latter stages of cement degradation 130,131 (pH ≈ 10). Silicate is also expected in the pore water of clay materials considered in certain repository concepts 132,133 for nuclear waste disposal. Despite the potential relevance of actinide−silicate complexation, thermodynamic data currently selected in the NEA-TDB are limited to U(VI)− and Am(III)− silicate species.…”
Section: An−silicatesmentioning
confidence: 99%
“…The presence of silicate is ubiquitous in most natural groundwater systems, where total silicate concentrations may reach up to 10 −3 M. 129 In cementitious environments, which are considered in some concepts for the disposal of low and intermediate level radioactive wastes (L/ILW), silicate concentrations of up to ∼5 × 10 −4 M have been determined in pore water during the latter stages of cement degradation 130,131 (pH ≈ 10). Silicate is also expected in the pore water of clay materials considered in certain repository concepts 132,133 for nuclear waste disposal. Despite the potential relevance of actinide−silicate complexation, thermodynamic data currently selected in the NEA-TDB are limited to U(VI)− and Am(III)− silicate species.…”
Section: An−silicatesmentioning
confidence: 99%
“…), August (14.75–14.85 m) and September (17.53–17.86 m), from FUN05‐01, are minor faults and shear zones that were the targets of other hydrological studies, in which the fluids were sampled for water chemical control and rock analyses (Reiller et al . ; Buckau et al . ).…”
Section: Hydrogeological and Geophysical Datamentioning
confidence: 95%
“…Reiller et al 15,16 performed inductive analysis of the existing migration law of Am and associated it with rare-earth elements; they concluded that when the pH of the solution is less than 7, between 7 and 8.5, and above 8.5, the main complex ions are RE 3+ , RECO 3 + and RE(CO 3 ) 2 À , and possibly RE(CO 3 ) 3 3À or higher-valence-state complex ions, respectively. Given similarities in the physicochemical properties of Am and rareearth elements, Maloubier et al 17 investigated the results of Am migration studies and concluded that the main forms of rare-earth carbonate ions in a water environment with pH 7-9 are RECO 3 + and RE(CO 3 ) 2…”
Section: àmentioning
confidence: 99%